(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Electrically conductive cotton fabrics were successfully prepared by a first free radical polymerization, assisted by a conventional pad-dry-cure textile technology and subsequent electroless deposition (ELD) of copper thin layers on cotton fiber surfaces. Pad-dry-cure takes a major role in the even uptake and penetration of the monomer [2-(methacryloyloxy)ethyl]trimethyl-ammonium chloride (METAC) solution throughout the cotton fabrics, making subsequent ELD plating of copper metal uniform. The surface electrical resistivity of as-prepared electro-conductive cotton fabrics varies from 10^3 to 10^-1Ω/sq, depending on the ELD conditions. The whole process is low cost, low chemical wastage and compatible with current wet processing in the textile industry, which provides a great potential in commercialization in a bulk scale.